Dogs in the Wroclaw Stronghold, 2nd Half of the 10th–1st Half of the 13th Century (Lower Silesia, Poland)—An Zooarchaeological Overview - Aleksandra Pankiewicz; Krzysztof Jaworski; Aleksander Chrószcz; Dominik Poradowski (Animals, 2021)
This article pertains to the issue of early medieval dogs (10th–mid-13th century) from the territory of Poland and Central Europe. The study is based on dog remains from the Wroclaw Cathedral Island (Ostrów Tumski), one of the most important administrative centres of early medieval Poland, the capital of a secular principality and the seat of diocese authorities. The main morphological and functional types of dogs living in Wroclaw and other parts of Poland were characterized on that basis. It has been concluded that the roles and perceptions of dogs were very ambiguous. On the one hand, they were hunting companionship for the elite and were considered a symbol of devotion and loyalty. On the other hand, dogs symbolised disgrace. In everyday life, these animals were sometimes abused, their skin was sometimes tanned and their bones modified into tools, and in exceptional cases, dogs were even eaten.